Growth and development of the leishmaniasis parasite in insect Aharms (Baghdad Science Journal, 2006)
The parasite Alchammannia Aaúlan Ahdma backbone and the other for Avgari and moves them alternately Vafiqra is Alannsan and Allbaún and other either Allavgari is an insect Aharms or sand fly of the genus deployed in the ancient world is different form the parasite and installed Albayukimaaúa in each of the Family is so when transmitted from host to another passes stages growth